Perbandingan Interval Training dan Circuit Training Terhadap Peningkatan Daya Tahan Anaerobic - Rocky Alexander Ramadhan; Muh. Isna Nurdin Wibisana; Pandu Kresnapati (Phsyical Education Health and Recreation Department of STKIP-YPUP Makassar, 2022)
This research was motivated by the weak anaerobic endurance of SSB Putra Mororejo U-16. This study aims to determine the effect of Interval Training and circuit Training on the anaerobic endurance of soccer players on the SSB Putra Mororejo U-16 team. This research is a quantitative research with a pretest-posttest control group design. The instrument used is the Running-based Anaerobic Sprint Test (RAST). The sample of this study were 20 players of SSB Putra Mororejo who were divided into two groups, namely the Interval Training group and the circuit Training group. Sampling using purposive sampling. The results of the normality and homogeneity test of the Interval Training and circuit Training groups have a value of more than = 0.05, both groups are normally distributed and homogeneous. The results of the paired sample t-test for the Interval Training group obtained a significance value of 0.002 <0.05 and the circuit Training group obtained a significant value of 0.001 <0.05. It was concluded that there was an effect of treatment Interval Training and circuit Training on anaerobic endurance. In the independent sample t test, Interval Training is more effective in increasing anaerobic endurance than circuit Training. This is evidenced by the data obtained that the increase in Interval Training has a percentage increase of 40.96% and circuit Training has an increase in the percentage of 24.96%. The conclusion in this study is that Interval Training is more effective than circuit Training in an effort to increase anaerobic endurance.